Learning teaching: A voyage of discovery - Arthur, Christine Shobana * (The Association of Science, Education and Technology, 2016)
The voyage of discovery is not in seeking new landscapes but in having new eyes ~ Marcel Proust. This paper is a reflection of a teacher’s experience of becoming critically reflective of his/her teaching practices. The teaching practices were triangulated through four lenses as proposed by Brookfield (1995): 1) autobiography as a learner and teacher, 2) colleagues’ experiences, 3) students’ eye and 4) theoretical literature. The first lens is a written reflective task on the journey of being a learner and now a teacher. This lens proves that one’s teaching practices are linked to how one was taught as a student. The second lens is the non-evaluative feedback provided by peers about the teacher’s teaching practices. The third lens is the feedback provided by students on certain specific concern that the teacher had highlighted. The final lens is the process of linking the practical aspects with theoretical aspects. Each lens reinforces one another. Consequently, this process helps one not only to become critical but also reflective of the teaching practices. Through this process a clear link was identified amongst the four lenses. The new perspective gained from this experience is indeed very crucial for all the academicians as it is a process of renewal of teaching practices by identifying discrepancies or conformities amongst the four lenses.